Use of palatally inserted mini-screw for upper molar distalization: A case series - Valliollah Arash; Sepideh Rezapour; Reza Ghorbanipour; Babak Amoian; Fateme Majdzade (Babol University of Medical Sciences, 2015)
Abstract Reports have shown that molars can be distalized successfully with virtually no orthodontic anchorage loss with an intraosseous anchorage, even with fully erupted second molars. The purpose of this study was evaluating the effects of mini-screws as skeletal anchorage for upper molar distalization. In this case series, three patients needing maxillary first molar distalization, were selected. mini-screw was inserted in the anterior part of the palate. The screws were anchored to the first premolars by transpalatal arch and immediately loaded (150-160 g) by 0.018-inch arch-wire and steel open-coil spring to distalize maxillary molars. The skeletal and dental changes were measured on cephalograms obtained before and after distalization. The amount of first molar distalization in the patients was 4 mm with 2°of tipping, 4 mm with 5°of tipping, and 3.5 mm with 2°of tipping respectively. Upper incisors and first premolars were stable during distalization.